Localizing a mobile robot with intrinsic noise - Picon, F. (2013)
Robot localization is a key barrier to providing natural interaction between 3D virtual characters, human users and mobile robots. Knowing where the robot is, relative to a known world-frame, is essential to directed gestures, gazes and expressions between the robot and the other real and virtual participants in a telepresence system. The intrinsic noise of robots is a flexible and robust, yet under-examined, source for localization information. Sounds that likely localize the robot are identified and separated from background noises using a support vector machine. The resulting sound-bearing data is combined with robot odometry using a particle filter. Experiments conducted in a noisy office environment show substantial improvement over odometry alone.